Pendampingan Meningkatkan Kemampuan Bahasa Inggris Melalui English Community: Konsep Praktis - Ibrahim, Muliaty; Sukmawati; Sujarwo; Meinar; Suciati (ABDI SAMULANG: Jurnal Pengabdian Kepada Masyarakat, 2024)
This journal documents the experiences and results of an English language learning program through engagement in English language communication. This research aims to measure the impact of direct interaction with native speakers and cultural context in improving English language skills, by providing practical guidance and describing the benefits gained through active participation in the English language community. Mentoring is carried out by connecting students with members of the English Community through online platforms or direct meetings. During mentoring, students are allowed to interact, ask questions, and learn directly from community members. The methods include group discussions, question-and-answer sessions, and language practice activities. English language learning assistance is carried out in four stages, namely; preparation, interaction, monitoring and evaluation. The results of English language learning assistance through the English Community are 1) increasing English language skills in speaking, listening, reading, and writing English after interacting with community members. 2) students seem more motivated to learn English after being involved in this assistance. 3) apart from improving English language skills, students also succeeded in building social networks with community members. They feel more comfortable and confident in interacting with native English speakers.